Room temperature ammonia sensor using side-polished optical fiber coated with graphene/polyaniline nanocomposite - Khalaf, A. L.; Mohamad, F. S.; Rahman, N. Abdul; Lim, H. N.; Paiman, S.; Yusof, N. A.; Mahdi, M. A.; Yaacob, M. H. (OSA Publishing, 2017)
We developed a highly sensitive side-polished plastic optical fiber coated with chemical synthesized graphene/polyaniline nanocomposite for ammonia gas sensing application. It was found that the optical sensor absorbance spectrum linearly increases with increasing ammonia concentrations. The experimental results revealed that the side-polished fiber sensor coated with graphene/polyaniline nanocomposite exhibited higher performance than the ones coated with only polyaniline. The proposed sensor demonstrated sensitivity, response and recovery times of 132.8 AU/%, 112 s, and 185 s, respectively, at room temperature. The superior sensing performance of the developed fiber sensor indicates its high efficiency for NH3 gas-sensing applications at room temperature.